Vliv polymorfismu genu pro prolaktin a jeho exprese v periferních mononukleárních buňkách na rozvoj autoimunitních chorob - systémového lupusu erythematodes, zánětlivých kloubních chorob (psoriatická a revmatoidní artritida) a psoriasis vulgaris - Hušáková, Markéta; Černá, Marie; Arenberger, Petr; Štolfa, Jiří; Lippert, Jan (Iga MZ ČR, 2012)
1. The study of mRNA immune cells expression (CD14 cells ) in patiens suffering from SLE, rheumatoid arthritis, psoriatic arthritis, psoriasis vulgaris and kontrol group 2. To complete the immunogenetic study with the SLE, RA, PV and PsA risk gene polymorphism, HLA class II and MIC-A and HLA class I and MIC-A respectively. 3. To complete the analysis of the -1149G/T SNP of the extrapituitary PRL promoter in patients suffering from RA, SLE, PV and PsA.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Immunity, Cellular; buněčná diferenciace; Prolactin; Cell Differentiation; prolaktin; biochemie; homeostáza; imunogenetika; psoriáza; buněčná imunita; revmatoidní artritida; Immunogenetics; Arthritis, Rheumatoid; Homeostasis; Lupus Erythematosus, Systemic; revmatologie; systémový lupus erythematodes; Psoriasis